ANALISA KESTABILAN BANGUNAN EMBUNG NUNUKA 1 - Seroy, Camela Apriani; Manoppo, Fabian J.; Rondonuwu, Steeva G. (JURNAL SIPIL STATIK, 2020)
Embung or can also be called a small dam is one of the buildings of water resources that can function to accommodate water, water conservation efforts, and can also control flooding even on a small scale. Some criteria for a shelter building are included in the embung criteria, including building height <15 meters calculated from the foundation to the highest elevation of the building and also the amount of water storage caused by construction is less than 500,000 thousand.Nunuka Embankment is one of the efforts carried out in order to overcome water shortages in East Bolangitang Sub district, where water deficits were identified in terms of needs and the availability of water in the sub-district.In order to avoid disasters caused by failure factors, embung buildings need to be reviewed for failure factors that are likely to occur similar to those used in potential failures in the construction of dams in general, namely building failure caused by the influence of hydrology and hydraulics, building failure caused because of the influence of water seepage, and building failure caused by the influence of the structure itself.In this thesis, the author has conducted an analysis using the parameters C (cohesion), Permeability (k), Poisson Ratio (n), Ã˜ (shear angle), gsat (gamma saturated), E (modulus of elasticity) and gunsat (gamma unsaturated) to calculate the potential for embung failure in terms of failure due to water seepage in the body of the reservoir and failure caused by the influence of the embung structure itself. Application Plaxis 8.5 is a tool used by the author to conduct a review of building safety factors, seepage that occurs in buildings and decreases that occur in dams in several scenarios then compared with the results of the same review using the Geostudio application.Â Keywords: Embung, Small Dam, Nunuka Embankment, Small Dam Stability, Safety Factor